DUSP10 constrains innate IL-33-mediated cytokine production in ST2hi memory-type pathogenic Th2 cells. Issue 1 (December 2018) - Yamamoto, Takeshi; Endo, Yusuke; Onodera, Atsushi; Hirahara, Kiyoshi; Asou, Hikari; Nakajima, Takahiro; Kanno, Toshio; Ouchi, Yasuo; Uematsu, Satoshi; Nishimasu, Hiroshi; Nureki, Osamu; Tumes, Damon; et al.
Abstract ST2hi memory-type Th2 cells are identified as a pathogenic subpopulation in eosinophilic airway inflammation. These ST2hi pathogenic Th2 cells produce large amount of IL-5 upon T cell receptor stimulation, but not in response to IL-33 treatment. By contrast, IL-33 alone induces cytokine production in ST2+ group 2 innate lymphoid cells (ILC2). Here we show that a MAPK phosphataseDusp10 is a key negative regulator of IL-33-induced cytokine production in Th2 cells. In this regard, Dusp10 is expressed by ST2hi pathogenic Th2 cells but not by ILC2, andDusp10 expression inhibits IL-33-induced cytokine production. Mechanistically, this inhibition is mediated by DUSP10-mediated dephosphorylation and inactivation of p38 MAPK, resulting in reduced GATA3 activity. The deletion ofDusp10 renders ST2hi Th2 cells capable of producing IL-5 by IL-33 stimulation. Our data thus suggest that DUSP10 restricts IL-33-induced cytokine production in ST2hi pathogenic Th2 cells by controlling p38-GATA3 activity. T helper 2 (Th2) cells and type 2 innate lymphoid cells (ILC2) respond differently to interleukin-33 (IL-33) stimulation. Here the authors show that a phosphatase, Dusp10, is expressed in Th2, but not ILC2, to dephosphorylate p38 kinase, reduce GATA3 transcription factor activity, and suppress the induction of IL-5 in response to IL-33.